Febrile Neutropenia and Hemorrhagic Stroke in a Thalassemia Major Patient - Sheikh-Taha, Marwan (2007)
A 36-year-old transfusion-dependent thalassemia major patient presented with febrile neutropenia and anemia. Deferiprone (L1) was discontinued as it was suspected to be the offending agent and prompt broad-spectrum antibiotic therapy was initiated after which the patient improved. After 11 days the patient developed hemorrhagic stroke and seizure whereby aspirin was discontinued and supportive therapy was given. Agranulocytosis is the most serious complication reported with L1 but, to the best of our knowledge, there are no previous reports on hemorrhagic stroke associated with the use of the agent, and hence, the etiology of the stroke which followed agranulocytosis caused by L1 remains obscure.